2021
DOI: 10.1177/02654075211025093
|View full text |Cite
|
Sign up to set email alerts
|

Relational maintenance, collectivism, and coping strategies among Black populations during COVID-19

Abstract: The current study, adopting community resilience and social creativity, explores Black individuals’ relational maintenance and collectivist strategies employed amid the COVID-19 pandemic. A sample of 410 Black adults across the United States answered open-ended web-based survey questions about identifiable shifts in relational dynamics and examples of mutual support exhibited among community members amid COVID-19. Findings include individuals implementation of media technologies to maintain communication and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…racially minoritized have developed coping skills and supports from earlier hardship they have experienced in their communities (e.g., systemic disparities, oppression, and racism), which prepared them to deal with the stressors associated with the COVID‐19 pandemic, while White or highly educated women were less prepared to deal with these stressors. Indeed, research in the United States documented increased emphasis on social support, communal interaction, and increased volunteerism in Black communities during COVID‐19 (Stamps et al., 2021 ), all factors that could promote individual and community resilience. Additionally, Black (57%) and Latin American (35%) children in the United States are more likely to reside in multigenerational households than white children (20%) (Cross, 2018 ), which may also have conferred resilience due to the additional support and childcare available in the home.…”
Section: Discussionmentioning
confidence: 99%
“…racially minoritized have developed coping skills and supports from earlier hardship they have experienced in their communities (e.g., systemic disparities, oppression, and racism), which prepared them to deal with the stressors associated with the COVID‐19 pandemic, while White or highly educated women were less prepared to deal with these stressors. Indeed, research in the United States documented increased emphasis on social support, communal interaction, and increased volunteerism in Black communities during COVID‐19 (Stamps et al., 2021 ), all factors that could promote individual and community resilience. Additionally, Black (57%) and Latin American (35%) children in the United States are more likely to reside in multigenerational households than white children (20%) (Cross, 2018 ), which may also have conferred resilience due to the additional support and childcare available in the home.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Stamps et al (2021) focused on how Black communities in the U.S. enacted relational maintenance and collectivist strategies during the pandemic. Stamps et al (2021) observed six themes: (1) reimagining of human connection (e.g., drive-by birthday parties), (2) increased established human communication tactics (e.g., writing letters), (3) adoption of new media literacies (e.g., email prayer requests), (4) monetary, emotional, or task-oriented support (e.g., help running errands), (5) leveraging skills and resources (e.g., meal prep for community members), and (6) institutional support (e.g., volunteering with social justice organizations). Stamps et al’s (2021) identity-centered approach enhances our understanding of diverse responses to COVIOD-19 and provides a foundation for more effective support for individuals with preexisting contextual vulnerabilities ( Pietromonaco & Overall, 2021 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…Many of the coping strategies within the Black community, such as familialism and spirituality, were hampered due to the safety measures and restrictions due to COVID-19 [ 25 , 53 ]. A few participants in our study did revert to their prayer life and scriptures to cope as cited in past studies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%